Produção e caracterização de anticorpos monoclonais contra InlA de Listeria monocytogenes - Mendonça, Marcelo (2008)
The food pathogen Listeria monocytogenes is the causative agent of listeriosis, a severe disease that courses with high rates of morbid and mortality. The conventional methods used for detection of this bacterium are laborious and expensive, requiring several days for final identification. Monoclonal antibody (Mab) based immunoassays used for rapid detection of L. monocytogenes have the advantage of being highly specific, particularly if the MAbs are directed against virulence factors conserved among pathogenic strains. Membrane protein internalin A (InlA) from L. monocytogenes is a well characterized virulence factor involved in its adhesion to and internalization in non-phagocytic cells of the host. This work reports on the production and characterization of a panel of MAbs against InlA of L. monocytogenes. For MAbs production, isogenic BALB/c mice were immunized with a recombinant fragment of InlA (rInlA) expressed in Escherichia coli. Five hybridomas secreting MAbs anti-rInlA were generated. The MAbs affinity constants (Ka) were among 7x107 L.mol-1 e 4x106 L.mol-1. The MAbs recognized specifically the species L. monocytogenes by indirect ELISA and Western blot. In indirect ELISA using live or heat-killed L. monocytogenes the MAbs recognized InlA only in bacteria that were grown in Listeria enrichment broth and that were not heated. Western blot analysis revealed that MAbs recognized a band around 88kDa in the L. monocytogenes strains, the molecular mass expected for InlA in its native form. The MAbs produced in this study have potential for use in immunoassays for the detection of L. monocytogenes.